The Generalized Composite Commodity Theorem: Stronger Support in the Presence of Data Limitations - Davis, George C. (The Review of Economics and Statistics, 2003)
Because of common data limitations, the existing testing framework for the generalized composite commodity theorem (Lewbel, 1996) is incomplete. This note clarifies and strengthens the testing procedure by implementing modified Bonferroni procedures. The conditions are established for consistency between the existing and modified Bonferroni tests. In an empirical application, the Bonferroni tests provide more powerful support for the generalized composite commodity theorem than is obtained from the existing test.